2015
DOI: 10.1093/pubmed/fdv041
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinician-clinical coder information handover following acute medical admissions: implication for using administrative datasets in clinical outcomes management

Abstract: The importance and applications of coded healthcare big data within the NHS is increasing. The accuracy of coding is dependent on high-fidelity information transfer between clinicians and coders, which is prone to subjectivity, variability and error. We recommend greater involvement of clinicians as part of multidisciplinary teams to improve data accuracy, and urgent action to improve abstraction and clarity of assignment of strategic diagnoses like pneumonia and renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…In a study of coding accuracy, Nouraei et al found that in nearly 9000 patient discharge records, clinician and clinical coder concordance for acute heart failure was excellent (kappa 0.92, 95% CI 0.88–0.95). 34 Despite potential coding inaccuracies and lack of clinical detail, assessment of clinical outcomes such as mortality and readmission rates using administrative data have been validated against medical records 35 as well as prospective registries. 36,37 Data for these analyses were derived from 3 states (CA, NY, and FL); generalizability to other states requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of coding accuracy, Nouraei et al found that in nearly 9000 patient discharge records, clinician and clinical coder concordance for acute heart failure was excellent (kappa 0.92, 95% CI 0.88–0.95). 34 Despite potential coding inaccuracies and lack of clinical detail, assessment of clinical outcomes such as mortality and readmission rates using administrative data have been validated against medical records 35 as well as prospective registries. 36,37 Data for these analyses were derived from 3 states (CA, NY, and FL); generalizability to other states requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer, differentiating between two synchronous tumours and extension of one tumour to multiple anatomical regions can be difficult. Identifying and abstracting clinical events into a coded language is prone to subjectivity, variability and error . This is not unique to the administrative data but its reduction through creating consensus between different centres could increase the generalisability of the data.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies from the US have explored using EHR data to measure outcomes (most often in combination with claims data), including a Stanford University research group in California, testing the use of EHRs specifically for prostate cancer [45][46][47]. However, poor data quality (including accuracy of clinical coding, which is prone to subjectivity, variability and error), issues regarding privacy, ownership and access, the use of different software systems across health care settings, and the difficulty and expense of mining clinical notes may limit their application [3,45,46,48].…”
Section: Limitationsmentioning
confidence: 99%